Carboxylate metallogels - an adventure in supramolecular chemistry - Zacharias, Savannah Clare (Department of Chemistry, 2018)
The field of supramolecular gels has attracted a great deal of attention as these versatile materials have been shown to be highly tunable and responsive to stimuli making them attractive for a multitude of potential applications such as drug delivery, energy and gas storage, and waste water treatment. Serendipity still plays a role in gel discovery. However, with the ever growing library of gels, design is becoming a greater possibility. Interactions involved in the formation of gels are closely related to those in the field of crystal engineering. There are two parts to this body of work. The first follows the exploration of factors that in uence carboxylate gel formation. The second is to examine the response of the iron(III)-carboxylate metallogels to external stimuli. For the gel formation, a range of small carboxylic acids (ligands), solvents, metal salts, and temperatures were used to investigate their respective roles. Systematic study showed that gels from ligands with carboxylate moieties in the ortho position passed the "inverted vial test" most consistently. Of the solvents used, only those with polarities between 4 and 7.2 resulted in gel formation. In general, the rate of gel formation increased with an increase in temperature. It was found that the nature of the counter ion in uences the outcome of gelation. Inorganic counter ions such as nitrate and halides resulted in gel formation, while organic counter ions such as acetylacetonate and oxalate did not. Characterisation was performed using thermal analysis, Fourier transform-infrared spectroscopy, microwave plasma atomic emission spectroscopy, scanning electron microscopy, and powder X-ray diffraction. It was found that the gels were ca. 95-99% solvent. The creation of xerogels, by oven or freeze drying, allowed for better characterisation. The response of the gel to stimuli was explored and they were shown to interact with their environment. Dyes bromocresol green and methyl orange were both sorbed, in different amounts, by the two carboxylate-iron(III) metallogels, Fe-5nite-DMF and Fe-tri-DMF. This was monitored using UV-visible spectrophotometry. Gas sorption experiments were performed using carbon dioxide, hydrogen, nitrogen, and water vapour. This was done in order to determine the response of selected xerogels to gas as well as to examine the effect of the drying method on pore size and gas sorption capability. In all cases, water vapour was adsorbed in the greatest quantity. A range of 184.54 cm³ (STP) g⁻¹ to 577.36 cm³ (STP) g⁻¹ at a relative pressure of 0.760 was seen. Separation of compounds with similar boiling points was attempted using Fe-phens-EtOH, Fe-tri-EtOH, and Fe-5nite-EtOH. The compounds, 2- and 3-methylpiperidine, disrupted the stabilising interactions within the gel and no separation took place. During the investigation into the role of an organic counter ion in gel formation, three novel crystal structures were obtained from iron(III) acetylacetonate and 2,6-pyridinedicarboxylic acid. The structures elucidated were found to be dependent on the temperature and length of time allowed for the reaction. Multiple factors in uence gel formation and with a better understanding of these, tunable materials for specific applications may be created.